Sunny with a chance: coming of age as coming out and coming into one's own - Maharaj, Upasna (Centre for Film and Media Studies, 2022)
The screenplay (creative production component) follows Sunny, a young South African Indian woman, who relocates to Cape Town to study fine art. She sets her eyes on a significant award, but makes the critical mistake of falling for her greatest rival. Despite facing crippling cultural expectations and biases, Sunny discovers that being different - and loving who she wants to love - is not a crime, but an imperfect truth. The screenplay explores the protagonist's first year at university, complicated by questions of identity, race, gender, sexuality and their intersection with tradition and culture in contemporary South Africa. Taking the form of a coming-of-age Indie drama (with an artistic twist), the main character embarks on a journey of self-discovery and learning, as she confronts these challenges. The reflective creative explication serves as an accompaniment to the screenplay. It is used to expound upon the creative process of writing the screenplay: highlighting key scenes, beats and decisions whilst interrogating the theoretical frameworks surrounding representations of ‘othered' groups - specifically queer womxn of colour - and their perception in society, aided by the lens of personal lived experience. This is followed by a review of the Indie and coming-of-age genres, in which the screenplay operates. The piece acts as a critical reflection intended to contextualise and justify the creative decisions made in the screenplay, so as to provide a means of accessing the larger themes and concerns at hand.